Navigating the transition: a qualitative exploration of first-year university students’ challenges, coping mechanisms and support systems - Pauviya Guna Segar; Azlina Mohd Kosnin; Lina Handayani (Intelektual Pustaka Media Utama, 2026)
This qualitative study examines the challenges, coping mechanisms, and support systems encountered by Malaysian university students during their first year. Using semi-structured interviews with 15 first- and second-year students, the study identifies key non-academic and academic challenges, coping strategies, and sources of support systems. Thematic analysis reveals that students face non-academic challenges such as independence and self-reliance, logistic and environmental challenges, increased autonomy and responsibility, and diminished family and social time. Academic challenges include time management and academic discipline, lack of guidance and support, challenges in course structure and content, academic overload and struggles with balancing university life, and external pressure and expectations. Coping mechanisms include homesickness and emotional support from others, lifestyle, time management and organization, hobbies and leisure activities, participation in university-supported socializing programs, and building friendships at the university. This study highlights the importance of tailored support interventions for first-year students and suggests improvements in university support frameworks. However, the research is limited by its small sample size and reliance on self-reported data. Future research could expand upon these findings with larger, more diverse samples and incorporate quantitative methods to validate and deepen insights into the first-year transition experience.